Neurotic disorders of nurses in psychiatric hospital wards - Tsirigotis, Konstantinos; Gruszczyński, Wojciech; Tokarska, Iwona (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. The work of nurses is associated with high level of stress. The profession of the nurse requires increased psychological effort (what is being related with observation of various states of the patient), personal involving in matters of suffering people and the increased responsibility for results of their own work. Aim of the study. The main aim of this work was to recognize frequency and kinds of neurosis disturbance appearance in the nursing environment. Material and methods. The research material was a group of nurses aged from 27 to 55. The research method was the "S-II" Symptom Check List by Aleksandrowicz. Results. In the majority of nurses (63.3%) appearance of neurosis disturbance is stated, and for 36.7% examined they had lasting character and required pharmalogical as well as psychotherapic treatment. In the group of neurosis disturbance dominated: sexual functions disorder (50%), social relations disorders (50%), psychosomatic symptoms (48%), tiredness symptom (42%), sleep disorder (41%) and also think disorder. No relationship was stated between "psychiatric seniority" and the neurosis symptoms, although there was a relationship with nurse job seniority generally. Conclusions. Neurotic disorders are serious health as well as social psychiatric nurses issue. Nursing Topics 2010; 18 (4): 461-468